2011
DOI: 10.4067/s0717-95532011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Situaciones Generadoras De Estrés en Los Estudiantes De Enfermería en Las Prácticas Clínicas

Abstract: RESUMENObjetivos: Conocer qué situaciones les resultan más estresantes a los alumnos de enfermería durante las prácticas clínicas, por curso y de forma global, así como la asociación de los factores causantes de estrés, con determinadas variables sociodemográficas y laborales. Método: Estudio transversal, descriptivo, comparativo y correlacional, realizado a 215 estudiantes de Enfermería matriculados durante el curso 2009-2010 en la Universidad de Murcia, utilizando como instrumento de medición una modificació… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 4 publications
0
8
0
21
Order By: Relevance
“…In terms of age, it was found that a relationship exists between a high chronic stress level and 25 years of age; furthermore, for a high level of academic stress, a significant association was found between situation EA1 and 23 years of age, and between situation EA3 and 18 years of age. Other studies differ with these results, indicating that 21-year-old students are at an increased risk for stress (e.g., Leiner & Jiménez, 2011;López & López, 2011). The difference between these authors and the work presented here stems from the fact that the association between the situations was more specific both for chronic stress as well as for the different situations of academic stress.…”
Section: Discussionmentioning
confidence: 46%
“…In terms of age, it was found that a relationship exists between a high chronic stress level and 25 years of age; furthermore, for a high level of academic stress, a significant association was found between situation EA1 and 23 years of age, and between situation EA3 and 18 years of age. Other studies differ with these results, indicating that 21-year-old students are at an increased risk for stress (e.g., Leiner & Jiménez, 2011;López & López, 2011). The difference between these authors and the work presented here stems from the fact that the association between the situations was more specific both for chronic stress as well as for the different situations of academic stress.…”
Section: Discussionmentioning
confidence: 46%
“…Se trata de un estudio de tipo transversal y de corte descriptiva (21) que utiliza como herramienta el cuestionario KEZKAK (18) , que mide factores causantes de estrés en las prácticas clínicas de alumnos de enfermería, presentando un alto nivel de validez y fiabilidad (22,23) . Consta de 12 ítems a contestar mediante una escala tipo Likert de 4 valores que comprende desde (0) "nada estresante" hasta (3) "muy estresante".…”
Section: Metodologíaunclassified
“…El nivel de estrés en prácticas formativas es un tema que interesa también en otras partes del mundo, como por ejemplo en España, donde López y López (12) detectaron que los estudiantes presentaron niveles de estrés altos durante sus prácticas clínicas, siendo más afectados aquellos estudiantes de segundo semestre de enfermería. En México, el estrés académico se presentó con mayor frecuencia en el género femenino, en los últimos años de la carrera de enfermería y durante las prácticas clínicas, según Marín et al (13).…”
Section: Nivel De Estrésunclassified